Prediction of favorable areas for sandy conglomerate reservoirs: a case study of the middle permian lower Wu’erhe Formation in the Wu’erhe Nose Uplift, Junggar Basin - Liu, Jun; Jia, Yingjie; Song, Tao; Chen, Zhen; Zhang, Ning (Frontiers in Earth Science, 2026)
In recent years, with the advancement of unconventional oil and gas exploration, tight sandy conglomerate reservoirs have attracted considerable attention due to their unique sedimentary characteristics and substantial resource potential. This study focuses on the tight sandy conglomerate reservoirs of the Lower Permian Wu’erhe Formation in the Wu’erhe Nose Uplift of the Junggar Basin. By integrating geological, well logging, and seismic data, this work provides a systematic evaluation of sedimentary microfacies, reservoir characteristics, and hydrocarbon accumulation patterns. The research reveals that the study area developed a fan delta–lacustrine sedimentary system, influenced by a northeastern sediment source and two major channels (W42 and F26). The second (P2w2) and third (P2w3) members of the Wu’erhe Formation are predominantly composed of subaqueous distributary channel sands within the fan delta front, exhibiting a sand-to-ground ratio of 40%–55% and favorable lateral continuity, which qualifies them as high-quality reservoir units. The sandy conglomerate reservoirs are characterized by a predominance of residual intergranular pores and intragranular dissolution pores, with pore structure marked by fine skewness and narrow throats. Differential compaction and selective dissolution during diagenesis have collectively contributed to a reservoir model described as “overall tight with local enrichment.” The primary hydrocarbon accumulation type is a structural-lithologic composite reservoir, jointly controlled by nose-like structures and lithologic boundaries. Through acoustic impedance inversion and seismic attribute analysis, the spatial distribution of dolomitic sandy conglomerate—exhibiting high impedance and high resistivity—was accurately delineated, leading to the identification of five new structural-lithologic traps. A comprehensive evaluation suggests that the second and third members of the Wu’erhe Formation, given their favorable reservoir properties and abundant hydrocarbon shows (including oil-rich and oil-impregnated intervals), represent the most prospective targets for “sweet spot” identification and large-scale horizontal well development in the study area. Finally, based on the development of oil-layer identification charts, specific testing recommendations were proposed for the W356 well area, and potential exploration targets were predicted.